Analisis Faktor Faktor Yang Mempengaruhi Struktur Modal Pada Perusahaan Real Estate Dan Property Yang Terdaftar Di Bursa Efek Indonesia - yosafat nababan, fery; Efriyenti, Dian (SCIENTIA JOURNAL, 2022)
The capital structure of real estate and property companies experienced fluctuating increases in different ways but the overall average decreased by -117%, the decline in the capital structure could be influenced by various factors such as liquidity and profitability. The purpose of this study was to determine whether liquidity and profitability affect the capital structure of real estate and property companies listed on the Indonesia Stock Exchange. The type of this research is quantitative. The data source of this research is secondary data. The technique of collecting data is by observation, literature study and documentation study. The analytical method is by testing classical assumptions, multiple linear regression and hypothesis testing with the help of the SPSS 25 program. The sample in this study was 27 companies listed on the IDX for the last 5 years, 2016-2020. Partial results of liquidity and profitability have no effect on capital structure. Simultaneously liquidity, profitability and affect the capital structure. In conclusion, H1 is rejected, H2 is rejected and H3 is accepted.